Long-term outcome of low-risk patients attending a rapid-assessment chest pain clinic. Issue 5 (4th October 2007) - Taylor, G L; Murphy, N F; Berry, C; Christie, J; Finlayson, A; MacIntyre, K; Morrison, C; McMurray, J
Abstract : Objective: To examine the long-term outcome of patients evaluated in a rapid assessment chest pain clinic (RACPC): are "low-risk" patients safely reassured? Design: Retrospective cohort study. Setting: Staff grade-led RACPC in an urban teaching hospital. Participants: 3378 patients (51% male), attending the RACPC between April 1996 and February 2000. Main outcome measures: Death, coronary mortality, morbidity and revascularisation over a median follow-up of 6 years. Coronary standardised mortality ratio (SMR). Results: 2036 (60.3%) patients were categorised as "low risk", 957 (28.3%) as having "stable coronary artery disease" and 214 (6.3%) as being an "acute coronary syndrome". During the study, 3.6% of patients in the low risk category, 11.9% in the stable coronary artery disease category and 24.6% in the acute coronary syndrome category died from coronary artery disease or had a myocardial infarction. 5.5%, 18.2% and 18.4%, respectively, died from any cause. Compared to the local population (coronary SMR = 100), our "low risk/non-coronary chest pain" cohort had a coronary SMR of 51 (95% CI 31 to 83), the "stable coronary artery disease" cohort 240 (187 to 308) and the "acute coronary syndrome" cohort 780 (509 to 1196). Conclusion: The RACPC was effective at triaging patients with chest pain. Patients identified as at "low risk" were unlikely to have an adverse coronary outcome and were appropriately reassured.